[RuIII(EDTA)(H2O)]− catalyzed oxidation of biologically important thiols by H2O2. Issue 22 (16th November 2016) - Sarkar, Papiya; Saha, Amrita; Chatterjee, Debabrata
Abstract: [Ru III (EDTA)(H2 O)] − (EDTA 4−  = ethylenediaminetetraacetate) catalyzes the oxidation of biological thiols, RSH (RSH = cysteine, glutathione, N-acetylcysteine, penicillamine) using H2 O2 as precursor oxidant. The kinetics of the oxidation process were studied spectrophotometrically as a function of [Ru III (EDTA)(H2 O)] −, [H2 O2 ], [RSH], and pH (4–8). Spectral analyses and kinetic data are suggestive of a catalytic pathway in which the RSH reacts with [Ru III (EDTA)] catalyst complex to form [Ru III ((EDTA)(SR)] 2− intermediate species. In the subsequent reaction step the oxidant, H2 O2, reacts directly with the coordinated S of the [Ru III ((EDTA)(SR)] 2− intermediate leading to formation of the disulfido (RSSR) oxidation product (identified by HPLC and ESI-MS studies) of thiols (RSH). Based on the experimental results, a working mechanism involving oxo-transfer from H2 O2 to the coordinated thiols is proposed for the catalytic oxidation. Graphical abstract: